2013
DOI: 10.1111/opo.12048
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fixation stability measured with MP‐1 and reading performance

Abstract: The study confirms that in people with visual impairment the reduced reading performance is correlated with fixation instability. Moreover, there is a strong relationship between reading speed and both the proportion of fixations falling within 2° and 4° and bivariate contour ellipse area values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…12,13 Fixation instability is related to slower reading in adults with macular disease. 15,16,22 In the present study, reading rate was associated with fellow eye instability, not with amblyopic eye instability, during binocular viewing conditions. Fixation instability may decrease the accuracy of forward saccades, causing the reader to miss the preferred landing position of the eye, the center of the word.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…12,13 Fixation instability is related to slower reading in adults with macular disease. 15,16,22 In the present study, reading rate was associated with fellow eye instability, not with amblyopic eye instability, during binocular viewing conditions. Fixation instability may decrease the accuracy of forward saccades, causing the reader to miss the preferred landing position of the eye, the center of the word.…”
Section: Discussionmentioning
confidence: 42%
“…Data showing that slow reading in strabismic amblyopia is related to making more saccades than controls support this hypothesis. 2,3,6 Other studies of eye movements in normally sighted 14 and visually impaired 15,16 adults have reported an association between fixation instability and slower reading. However, no studies have assessed the relationship between ocular motor dysfunction and reading in amblyopic children without strabismus (ie, anisometropic amblyopia).…”
mentioning
confidence: 99%
“…Previous studies have shown that fixational stability is positively correlated with reading speed (Amore et al, 2013; Amore et al, 2014; Crossland et al, 2004; Crossland, Dunbar, & Rubin, 2009), face perception (Seiple, Rosen, & Garcia, 2013), and visual search (Kwon et al, 2013; Walsh & Liu, 2014). Consistent with these findings, we found that the development of a PRL led to better performance in visual recognition (19% improvement) and search performance (22% improvement), confirming the key role of a stable PRL for pattern recognition in peripheral vision.…”
Section: Discussionmentioning
confidence: 97%
“…1012 Fixation instability has been implicated in slower reading in normally-sighted 13 and visually impaired adults with macular disease, albinism, or glaucoma. 14,15 More recently, we reported that fixation instability, and an increased number of forward saccades was associated with slower reading in children with anisometropic amblyopia (Kelly, et al J AAPOS 2017;21:e10 Abstract 024). Unstable fixation may make it difficult to plan and/or execute accurate forward saccades during reading.…”
mentioning
confidence: 96%